Comparison of three indices of relative income deprivation in predicting health status. (February 2022) - Gero, Krisztina; Yazawa, Aki; Kondo, Naoki; Hanazato, Masamichi; Kondo, Katsunori; Kawachi, Ichiro
Abstract: Relative income deprivation (RID) is a known risk factor for poor health. Previous research has proposed several measures to assess RID, e.g., Income Rank and the Yitzhaki Index. Hounkpatin et al. (2020) presented a new approach – the C R ˜ i index – to account for the observation that individuals are more sensitive to the differences in incomes of others who are closer to them, rather than to comparisons with incomes of others far above them. Using a Japanese nationwide cohort of older adults (n = 62, 438; mean [SD] age: 73.0 [5.6] years), this study compared the performance of alternative indices of RID in predicting health outcomes (depressive symptoms, functional capacity, and self-rated health), as well as the use of alternative C R ˜ i index weights ( α weight range: −0.9 to 0.9). When 0 < α < 1, higher income differences lead to a more significant increase in relative deprivation, while when −1< α <0, excessively high incomes contribute less to the relative deprivation of lower income individuals in the same reference group. Results showed that all measures of relative income deprivation were associated with deteriorating mental and physical health among older Japanese adults. However, while the C R ˜ i index consistently outperformed the Yitzhaki Index, this did not hold true invariably when compared to the Income Rank – depending on the health outcome and the reference group. Also, while negative α parameters showed a good statistical fit in most models, the findings were not conclusive – the best-fitting C R ˜ i weight parameters ranged from −0.9 to 0.9. Therefore, a clear direction for the contribution of higher incomes to relative deprivation could not be established based on the study population. Highlights: Relative income deprivation was consistently associated with mental and physical health. The novel C R ˜ i index consistently outperformed the Yitzhaki Index. The performance of the C R ˜ i index was comparable to the Income Rank. No conclusive evidence was found on the direction or magnitude of the best-fitting α parameter.